MANAJEMEN PENINGKATAN PROFESIONALISME GURU DI SEKOLAH DASAR NEGERI PADASUGIH 01 KECAMATAN BREBES KABUPATEN BREBES - Anita Endah Sekar Sari; Noor Miyono; Titik Haryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT: The context of this study is the management of improving teacher professionalism at SDN Padasugih 01. The purpose of this study was to analyze the planning, organizing, mobilizing, and monitoring and evaluation in improving teacher professionalism at SDN Padasugih 01. This study used a qualitative descriptive method, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the management of improving teacher professionalism carried out has a significant role in improving professionalism. The principal at SDN Padasugih 01 has implemented various strategies for improving professionalism which include activities 1) planning to improve teacher professionalism, the findings in the RKS did not find a plan to improve teacher professionalism because the principal compiled it separately from the RKS; 2) organizing teacher professionalism improvement, the findings were that teachers did not use assignment letters and SPPD from the school because training invitations came directly from the center so that they had to shift the budget to BOSP; 3) driving teacher professionalism improvement, the findings were that the principal had not given physical awards to teachers' efforts to improve their professionalism; and 4) supervision of teacher professionalism improvement, the findings are that the principal has not routinely held good practice activities as a result of teacher professionalism improvement activities. This study suggests that schools be more proactive in encouraging their teachers to improve their professionalism. Policy support from the government and local education offices is also considered essential to ensure that these programs can run optimally and sustainably. In conclusion, effective management in improving teacher professionalism will have a positive impact on the quality of learning and student learning outcomes. Keywords: Planning, Organizing, Actuating and Evaluation Supervision, Teacher Professionalism.